Analysis And Evaluation Of Pharmacist Power Needs With The WISN Method In The Pharmaceutical Installation Of Haji Hospital Surabaya - Subhan, Muhammad; Wardani, Ratna; Ramdani, Dewi (Universitas Muhammadiyah Sidoarjo, 2021)
The success of the hospital in carrying out its functions is influenced by several factors, among which the most dominant is human resources. Human resources are one of the important factors to be able to provide quality and comprehensive services in health services and are the key determinants of the rate and quality of services. The method of calculating needs based on workload (WISN) is an indicator that shows the amount of workforce required for health facilities based on workload, so that the allocation / relocation of labor will be easier and more rational. This research is a descriptive observational research with qualitative data analysis with purposive sampling method, namely the sampling technique by determining certain criteria. The HR category that will be calculated is the pharmacist in the Pharmacy Installation of the Surabaya Haji Hospital and results in a calculation of the total need for pharmacists of 24 people, compared to the current number of pharmacists of 20 pharmacists, the addition of pharmacists is 4 people in the Home Pharmacy Installation Haji Hospital Surabaya. The current number of fulfilled personnel from the calculation results only fulfills 83% of the ideal amount generated by the WISN method. With the obstacles faced such as the large workload of clinical pharmacy services that are carried out every day. To anticipate this, it is necessary to fulfill the need for pharmacists.